Creativity in crisis communication: a systematic review - Rasa Smaliukienė (Creativity Studies)
This systematic review explores the concept of creativity in crisis communication, a widely used but poorly conceptualised phenomenon. It draws on empirical research and case studies to highlight the diversity of creative approaches during major crises such as natural disasters, health crises, or conflicts. The focus is particularly on situations where these crises are protracted, and creativity is required to deal with the “fog of warning” caused by repeated alerts. It is also important to exercise creativity in order to control the meaning of information and combat the spread of misinformation and conspiracy theories. Creativity in crisis communication during major crises is described as the dynamic generation of novel and contextually relevant strategies using unconventional or metaphorical elements to engage audiences, reshape their understanding, and drive behavioural change for effective crisis resolution and recovery. The study provides a framework for understanding creativity in crisis communication by synthesising existing academic knowledge. Using the preferred reporting items for systematic reviews and meta-analyses methodology, 42 articles were analysed and categorised into three areas of communication: meaning making, behaviour framing, and reputation preservation. The framework illustrates the multiple facets of creativity: metaphorical creativity promotes critical reflection; visual representation enhances accessibility; humour and creative solutions engage and motivate diverse audiences; artistic elements, serious games and creative scenarios facilitate behaviour change. This framework underscores the critical role of creativity in crisis contexts, bridging the gap between standard communication and innovative, contextually relevant strategies in crisis communication strategies.